Arte da montagem espacial em obras de realidade virtual - Brito, Caio Victor da Silva (2023)
When experiencing immersive audiovisual works for virtual reality (VR), we notice that the interactivity of the viewer's gaze around the 360° plane is largely responsible for the framing of the spherical scene, that is, the way a VR work will be experienced is unique to each individual. In this way, it prompts us to reflect on how spatial composition and the arrangement of 360° shots are developed according to the logics of artistic creation for VR. Therefore, we investigate how the construction of 360° editing takes place based on a visual composition approach for the spherical plane in contemporary immersive virtual reality works, whether interactive or not. The foundations of this dissertation encompass studies on new media and virtual reality, how they correlate with the history and language of cinema, in light of the knowledge developed through practical developments within the Intervalos e Ritmos (#ir!/Projet'ares Audiovisuais/PPGARTES/UFC) group, as well as essays analyzing the aesthetic and poetic experiments of our own immersive creations, influenced by Szafir's (2016) provocation in dialogue with Manovich (2013) regarding "when cinema becomes Design," and the art of motion graphics (Szafir, 2016). By engaging with artists such as Anderson and Huang (2017), Colinart (2016), Kranot (2021), Vautier (2017), and Zandrowicz (2016-2022), among others, as well as authors like Murray (1997), Grau (2003), Flusser (2005), Brillhart (2015), Alger (2015), Mateer (2017), Tricard (2018), Doyle (2021), Bylieva (2021), among others, we highlight distinct aesthetics of creation and accessible pedagogies for the artistic poetics of virtual reality that contribute to its dissemination among artists, audiovisual creators, and, why not, amateurs.